On Equity and Public Pricing in Developing Countries - Klaus Mohn (Statistics Norway, Research Department, 1994)
With address to developing countries, this paper derives some formulae for the optimal price structure for publicly provided private goods. A general equilibrium model is examined, which makes it possible to incorporate features like distributional social objectives and public profit constraints in the analysis. The model identifies different sources which may cause the optimal public price structure to deviate from marginal cost pricing in a second-best optimum. The main result is that the optimal public price structure includes an implicit subsidy on commodities which are consumed relatively intensely by transfer-deserving households, whereas the same price structure involves an implicit tax on publicly provided luxuries.
Keywords: D63; H42; O15; 330; Equity; publicly provided private goods; income distribution.